2020
DOI: 10.1089/heq.2019.0126
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes and Documentation Status Among Latina Women: A Systematic Review

Abstract: The impression that Latinas experience paradoxically good pregnancy outcomes in the United States persists, despite evidence showing that these outcomes are not enjoyed by all Latina subgroups. We conducted this systematic literature review to examine the relationship between documentation status and pregnancy outcomes among Latinas. Methods: This review synthesizes empirical evidence on this relationship; examines how these studies define and operationalize documentation status; and makes recommendations of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
16
1
Order By: Relevance
“…There is an urgent need to address coverage gaps for all pregnant people in the US, particularly as research has found higher rates of pregnancy complications and postpartum depression among undocumented people. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need to address coverage gaps for all pregnant people in the US, particularly as research has found higher rates of pregnancy complications and postpartum depression among undocumented people. 22 …”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to address coverage gaps for all pregnant people in the US, particularly as research has found higher rates of pregnancy complications and postpartum depression among undocumented people. 22 Indigenous people, particularly Indigenous rural residents, are at increased risk for severe maternal morbidity and mortality and may face unique barriers to care. 23,24 For example, relationships created by US treaty obligations may enable enrolled tribal members to access health care via the IHS, but do not always provide health insurance coverage for other health care clinicians or facilities.…”
Section: Jama Health Forum | Original Investigationmentioning
confidence: 99%
“…These findings could be another expression of so-called Latina paradox. This paradox is examined in a systematic review 24 of a large number of studies showing that, despite lower economic status, less access to medical care, Latina’s appear to have fewer complications and better pregnancy outcomes compared with other minority groups. This paradox is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…But nation of birth and documentation status may play a significant role. 24 Unfortunately, the data set used for our analysis does not allow us to shed any additional light on these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the associations between immigrant legal status and health and development are limited because few studies directly measure legal status; most studies rely on imperfect proxy measures of unauthorized immigrant status (Richardson et al 2020). Existing evidence suggests that, compared to documented Hispanic foreign-born and U.S.-born mothers, Hispanic unauthorized immigrant mothers have similar or lower levels of preterm birth and low birthweight but higher levels of delivery complications and postpartum depression (Richardson et al 2020). Access to public benefits programs promotes health, but many immigrant families are ineligible.…”
Section: Political and Legal Contextsmentioning
confidence: 99%